Breeding biology, diet and vocal repertoire of White-rumped Monjita Xolmis velatus - Gussoni, Carlos Otávio Araujo; Tinti, Maria Clara [UNESP]; Gomes, Arthur Monteiro; Ramassotti, Luiz Carlos; Machado, Rogério Carlos; Cetani, Lucas Ezequiel Rubio; Michelotto, Alexandre S.; Gonzales, Manuel (British Ornithologists' Club, 2024)
Although generally common in parts of eastern and southern South America, the biology of White-rumped Monjita Xolmis velatus is poorly known. We aimed to augment existing knowledge with previously unpublished data concerning its breeding biology, diet and vocal repertoire. We studied three nests and one encounter outside the nest. To complement our field data, we searched the literature and 7,895 media submitted to online citizen science platforms. We present a list of food items consumed by the species and provide the first detailed description of its vocal repertoire, identifying four different call types. All nests were cups sited low above ground (0.3-4.0 m). The breeding season in Brazil extends at least from June to January. In two nests, more than one adult fed the nestlings. At one, nestlings were fed insects of six orders (mainly Coleoptera), spiders, earthworms, one myriapod, and a lizard (Kentropyx aff. paulensis).